Discovery of novel mycoviruses from fungi associated with mango leaf spots - Qihua Wang; Mengyi Chen; Yanling Xie (Frontiers in Microbiology)
Mango (Mangifera indica) is a commercially significant fruit crop cultivated globally. However, leaf spot diseases are common in mango orchards, which severely impact the yield. Mycoviruses hold promise as potential biocontrol agents. To investigate this possibility, fungi were isolated from mango leaf spot lesions, resulting in the identification of six strains that contained double-stranded RNA (dsRNA). Through BLASTx analysis of the NCBI non-redundant database, 27 mycovirus-related contigs were identified, which corresponded to 10 distinct viruses grouped into 8 lineages: Alternaviridae, Chrysoviridae, Partitiviridae, Polymycoviridae, Orthototiviridae, Deltaflexiviridae, Narnaviridae, and Bunyaviricetes. Full genomic sequences of these viruses were characterized and confirmed to be associated with their host fungi. The findings included six novel mycoviruses, three previously unreported viruses discovered in new hosts, and one virus strain. These results highlight the diversity and taxonomy of mycoviruses found in fungi associated with mango leaf spots.